Collaborative Virtual Reality in Higher Education: Students' Perceptions on Presence, Challenges, Affordances, and Potential - Laine, Teemu H.; Lee, Woohyun (IEEE Transactions on Learning Technologies, 2024)
The metaverse is a network of interoperable and persistent 3-D virtual worlds where users can coexist and interact through mechanisms, such as gamification, nonfungible tokens, and cryptocurrencies. Although the metaverse is a theoretical construct today, many collaborative virtual reality (CVR) applications have emerged as potential components of the metaverse. The demand for distance learning in higher education grew rapidly with COVID-19, but it has many challenges such as low motivation, low interest, and lack of suitable environment. We investigated the suitability of CVR applications for higher education by analyzing 9 existing CVR applications and then conducting a mixed-method user study on the Spatial CVR application with 41 university students (24 females, 17 males, mean age: 23.5). The results revealed 14 challenges, 13 affordances, and 20 ideas for using CVR in higher education. Moreover, lack of instructions, cybersickness, discomfort, limited embodiment, and limited sensory stimulation were among the identified issues that may inhibit the sense of presence in Spatial. Based on the findings, we proposed 13 guidelines to facilitate providing CVR learning in higher education and concluded that CVR has some use cases in higher education to complement conventional methods. These results can be useful for researchers, developers, and educators who seek to be at the forefront of adopting CVR as a part of the metaverse to come.
Keywords: Affordances; Challenge; Collaboration; Collaborative learning; Metaverses; Presence; Three-dimensional display; Usability; User study; Affordances; challenges; collaborative learning; metaverse; presence; user study; virtual reality (VR)